Environmental sustainability application in the Professional School of Fluid Mechanical Engineering – UNMSM - Arámbulo Manrique, Miguel Ernesto (2022)
The study deals with the implementation of environmental sustainability in the Professional School of Fluid Mechanics Engineering of the National University of San Marcos (EPIMF-UNMSM, 2022), since it is a commitment of every university to implement an Environmental Protection Plan within the licensing framework. , but it is also an institutional commitment, in the study a survey is applied that was validated and in it the students perceive that the university does not give importance to environmental sustainability, that is, the values ​​of Corporate Social Responsibility (CSR) and Responsibility Social University (RSU) are not appreciated, the commitment to Environmental Sustainability of students and teachers, apparently, is not favorable, both actions are analyzed and how they are related, corroborating that the UNMSM, according to this result, does not identify with Environmental Sustainability or RSU. The analysis determines that USR is in the background for the university, but the student's interest in Environmental Sustainability is appreciated, a fact that is concomitant and notable. This study is a starting point to propose to the university and the research that they must initiate a better environmental management and the responsibility that it must assume as an institution committed to this type of values.